Criteria to Identify a Potential Deceased Organ Donor: A Systematic Review. Issue 8 (August 2018) - Squires, Janet E.; Coughlin, Mary; Dorrance, Kristin; Linklater, Stefanie; Chassé, Michaël; Grimshaw, Jeremy M.; Shemie, Sam D.; Dhanani, Sonny; Knoll, Gregory A.
Abstract : Objectives: To systematically review the global published literature defining a potential deceased organ donor and identifying clinical triggers for deceased organ donation identification and referral. Data Sources: Medline and Embase databases from January 2006 to September 2017. Study Selection: All published studies containing a definition of a potential deceased organ donor and/or clinical triggers for referring a potential deceased organ donor were eligible for inclusion. Dual, independent screening was conducted of 3, 857 citations. Data Extraction: Data extraction was completed by one team member and verified by a second team member. Thematic content analysis was used to identify clinical criteria for potential deceased organ donation identification from the published definitions and clinical triggers. Data Synthesis: One hundred twenty-four articles were included in the review. Criteria fell into four categories: Neurological, Medical Decision, Cardiorespiratory, and Administrative. Distinct and globally consistent sets of clinical criteria by type of deceased organ donation (neurologic death determination, controlled donation after circulatory determination of death, and uncontrolled donation after circulatory determination of death) are reported. Conclusions: Use of the clinical criteria sets reported will reduce ambiguity associated with the deceased organ donor identification and the subsequent referral process, potentially reducing the number of missed donors and saving lives globally through increased transplantation. Abstract : Supplemental Digital Content is available in the text.